Hubungan Profil Sensori dengan Perilaku Makan Anak Autism Spectrum Disorder (ASD): The Relationship between Sensory Profiles and Eating Behaviors in Children with Autism Spectrum Disorder (ASD) - Rapali, Stella Gracia Jessica; Lestari, Nur Eni; Anindya, Isti; Suryadi, Bambang (MPI Press, 2023)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by deficits in social communication, limited interests, and repetitive behavior. In children with ASD, eating disorders are characterized by eating behavior, namely food selectivity. Objectives: This research was conducted to look at the relationship between sensory profiles and eating behavior in children with ASD in 2022. Method: Using correlational observational research with a cross-sectional design. Determining the sample size was carried out using consecutive sampling and it found that 97 respondents were parents of children with ASD who met the inclusion and exclusion criteria on the Autism Spectrum Disorder Care Platform. Data collection was carried out online using standard Short Sensory Profile (SSP) and Child Eating Behavior Questionnaire (CEBQ) instruments. Bivariate statistical test, this study uses Spearman correlation. Result: From the research results, it was found that the relationship between the sensory profile and the eating behavior of children with ASD was 0.138 or p-value> 0.05. Conclusion: There is a relationship between sensory profiles and the eating behavior of children with autism spectrum disorder (ASD) at the ASD Research Center in 2022.